Carbon dioxide induced structural phase transition in metal–organic frameworks CPO-27. Issue 26 (22nd June 2020) - Pato-Doldán, Breogán; Rosnes, Mali H.; Chernyshov, Dmitry; Dietzel, Pascal D. C.
Abstract : The framework of CO2 saturated CPO-27 is deformed below 110 K into a superstructure of the original honeycomb structure. Abstract : A phase transition occurs in metal–organic framework CPO-27-M (M = Co and Zn) below ∼110 K in CO2 atmosphere. The phase change involves the collective rearrangement of the inorganic chains and the organic ligands of the honeycomb framework. The new phase represents a superstructure of the original unit cell with doubled a and b axes, in which the cylindrical pore of the original phase transforms into two different pores.